Anticancer potential of acetone extracts from selected Potentilla species against human colorectal cancer cells - Augustynowicz, Daniel; Lemieszek, Marta Kinga; Strawa, Jakub Władysław; Wiater, Adrian; Tomczyk, Michał (Frontiers in Pharmacology, 2022)
Cinquefoils have been widely used in local folk medicine in Europe and Asia to manage various gastrointestinal inflammations and/or infections, certain forms of cancer, thyroid gland disorders, and wound healing. In the present paper, acetone extracts from aerial parts of selected Potentilla species, namely P. alba (PAL7), P. argentea (PAR7), P. grandiflora (PGR7), P. norvegica (PN7), P. recta (PRE7), and the closely related Drymocalis rupestris (syn. P. rupestris) (PRU7), were analysed for their cytotoxicity and antiproliferative activities against human colon adenocarcinoma cell line LS180 and human colon epithelial cell line CCD841 CoN. The analysis of secondary metabolite composition was carried out by LC-PDA-HRMS. The highest TPC and TTC were found in PAR7 (339.72 and 246.92 mg gallic acid equivalents (GAE)/g extract, respectively) and PN7 (332.11 and 252.3 mg GAE/g extract, respectively). The highest TPrC, TFC, and TPAC levels were found for PAL7 (21.28 mg catechin equivalents (CAT)/g extract, 71.85 mg rutin equivalents (RE)/g extract, and 124.18 mg caffeic acid equivalents (CAE)/g extract, respectively). LC-PDA-HRMS analysis revealed the presence of 83 compounds. The presence of tri-coumaroyl spermidine was demonstrated for the first time in the genus Potentilla. Results of the MTT assay revealed that all tested extracts decreased the viability of both cell lines. The highest selectivity was demonstrated by PAR7, which effectively inhibited the metabolic activity of LS180 cells (IC50 = 38 µg/mL), while at the same time causing the lowest unwanted effects in CCD841 CoN cells (IC50 = 1134 µg/mL). The results of LDH assay revealed that all tested extracts were not cytotoxic against normal colon epithelial cells, whereas in the cancer cells, all compounds significantly damaged cell membranes, and the observed effect was dose-dependent. The highest cytotoxicity was observed in LS180 cells in response to PAR7, which, in concentrations ranging from 25 to 250 µg/mL. Performed studies have revealed that all Potentilla species may be useful sources for anti-colorectal cancer agents; however, additional research is required to prove this definitively.